Pelayanan Administrasi Berhubungan dengan Kepuasan Pasien - Deska Herliani; Tresna Fatmawati; Riana Dewi (Jurnal Kesmas Asclepius, 2022)
This study aims to determine the relationship between the quality of administrative services (reliability, responsiveness, assurance, tangibles, and empathy) and patient satisfaction in the ASRI Medical Center Palembang dental clinic. This research method is a quantitative method with a cross-sectional design. The study's results obtained p value = 0.015 with OR = 3.273, meaning that good administrative services have a 3.273 times higher chance for patients to be satisfied than poor administrative services. In conclusion, there is a significant relationship between administrative services and patient satisfaction at the ASRI Medical Center Palembang Dental Clinic. Keywords: Administration, Satisfaction, Patients, Services